Synthesis of Dilute Phosphorous-Embedded Co Alloy Films on a NiSi Substrate with a Superior Gap-Filling Capability for Nanoscale Interconnects. Issue 4 (14th April 2021) - Fang, Jau-Shiung; Wu, Yu-Lin; Cheng, Yi-Lung; Chen, Giin-Shan
Abstract : Nanoscale cobalt interconnection wire has a lower mean free path of electrons to reduce the electrical resistivity, therefore it has been increasingly studied as a promising interconnect material to replace the conventionally used copper in state-of-the-art nanoscale devices. This process further limits the space for barrier/seed layer deposition to conformally fill the narrow trenches/contact holes in nanoscale devices. Thus, an electrochemical approach not involving a conventional high-resistivity barrier is presented to study the gap-filling capability and properties of Co(P) films with a controlled composition on a NiSi substrate. Examining electrodeposited Co(P) films reveals that the composition is determined mainly by the deposition potential instead of the amount of NaH2 PO2 in the electrolytes, yielding a film with a phosphorous concentration lower than 2.62 at.%. The lightly doped Co(P) film has an hexagonal close-packed Co structure with phosphorous atoms at the interstitial lattice site. A chronoamperometry study on the current transient during the electrochemical deposition indicates that NaH2 PO2 addition can enhance the deposition of the Co(P) films. Hence, the Co(P) film developed here is capable of gap filling nanoscale trenches up to an aspect ratio of 5 and is practical as a contact plug material for NiSi in nanoscale devices.